PENGARUH ENTREPRENEURSHIP, BUSINESS COACHING, MENTORING DAN KOMUNITAS KREATIF TERHADAP KINERJA INDUSTRI KREATIF: Studi pada Industri Kreatif yang Tergabung dalam Malang Creative Fusion - Anjaningrum, Widiya Dewi; Sapoetra, Yudistira Arya (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2018)
This study aims to determine the influence of entrepreneurship, business coaching, mentoring and creative communities both simultaneously and partially to the creative industries performance. Entrepreneurship is reflected by the instrumental, prestigious, sociable, takeover, self-sufficiency, hard work, self-confidence, innovative, leadership, action oriented, simple thinking and focus on effort. While business coaching and mentoring is reflected by the forms of training and coaching activities provided by the government and others, the frequency of training and coaching, the duration of assessment and implementation. While the creative community is measured on four aspects, that are, the nature, membership, way of working and relationships with other communities. Performance is indicated by customer growth rate, customer satisfaction level, customer satisfaction level, number of new products, level of job satisfaction and productivity level. Collecting data is done through direct survey to the research object, the creative industry actors who are members of MCF (Malang Creative Fusion). The results show that entrepreneurship, business coaching, mentoring and creative community have simultaneously influence to the creative industries performance. Also, that four independent variables, partially, has positive significant influence to the creative industries performance. So, in order to achieve optimal creative industry performance, it is expected that entrepreneurship in each creative industry actors, collaboration and synergy of quadruple helix are improved.